RELIGIOUS EDUCATION IN BRAZIL: COMPARING THE EXPERIENCES OF SERGIPE PERNAMBUCO PERSPECTIVE AND CONSTRUCTION OF TOLERANCE - Aurenéa Maria de Oliveira; Péricles Moraes de de Andrade Jr; Daniela dos Santos Rezende; José Eraldo Neves Ribeiro (Editora da Universidade de Santa Cruz do Sul, 2013)
This article aims to analyze the limits of application of the provisions of Article 33 of Law 9475 of July 22, 1997 in the school of education public networks of Sergipe and Pernambuco. Some guiding questions are: law enforcement can avoid proselytizing? How are the contents and standards for qualification of teachers? The article starts with the premise that in part the application of Law No. 9475 can not avoid proselytizing in Religious Education, a trend observed in the content in the standards for qualification of teachers in the Religious Education and in the involvement of religious organizations in the educational practice.